Abstract Word Definition in Patients with Amnestic Mild Cognitive Impairment - Soo Ryon Kim; SangYun Kim; Min Jae Baek; HyangHee Kim (Behavioural Neurology)
The aims of this study were to investigate concrete and abstract word definition ability (1) between patients with amnestic mild cognitive impairment (aMCI) and normal adults and (2) between the aMCI subtypes (i.e., amnestic single-domain MCI and amnestic multidomain MCI; asMCI and amMCI) and normal controls. The 68 patients with aMCI (29 asMCI and 39 amMCI) and 93 age- and education-matched normal adults performed word definition tasks composed of five concrete (e.g., train) and five abstract nouns (e.g., jealousy). Task performances were analyzed on total score, number of core meanings, and number of supplementary meanings. The results were as follows. First, the aMCI patients scored significantly poorer than the normal controls in only abstract word definition. Second, both subtypes of aMCI performed worse than the controls in only abstract word definition. In conclusion, a definition task of abstract rather than concrete concepts may provide richer information to show semantic impairment of aMCI.